PENERAPAN METODE SIMULASI DALAM PEMBELAJARAN FIKIH IBADAH BAGI SISWA DI MTS YMPI SEI TUALANG RASO TANJUNG BALAI - nurhayani nurhayani (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
ABSTRACT The purpose of this study is to identify and analyze the Application of Simulation Method  in Worship Fiqh Learning for Students of Mts YMPI Sei Tualang Raso Tanjungbalai, which includes the application of simulation  methods in the learning fiqh of worship for students, process of simulation  method that implemented  by teacher, effective simulation methods that used by teachers, using qualitative methods. In data analysis the researcher used qualitative analysis technique to the process of data reduction, data presentation and drawing conclusions.There are three findings in this study: That in the application of simulation methods can be concluded that there are three things to high lighted, there are: 1. Planning: The teacher planning or designing scenario and discussing the steps with students. 2. Before doing the simulation, in advance, the teacher makes the students into some groups then gives directions as well as the simulation scenario to each group, then 3. The teacher close the simulation by giving conclusions on the implementation of the simulation.The second finding: That in the process of applying simulation method in the learning worship fiqh for students in MTs YMPI Sei Tualang Raso Tanjungbalai, student activity is also a major influence in the successful implementation of the simulation, and based on the research findings in the field can be found  that the students are very enthusiastic about the simulation  method which are applied in the study of worship fiqh, students are  more fastly understand on reading prayers, verses and the ordinances taught in Worship Fiqh material.The third finding: That the application of simulation method in the learning worship fiqh for students in MTs YMPI Sei Tualang Raso Tanjungbalai is very effective to apply due to application of simulation method enhances the understanding and student learning outcomes in learning worship fiqh.The simulation method is very effective to apply in  the worship fiqh  learning, this reflects in the attitudes of students are very enthusiastic about the application of simulation method and the application of simulation methods in fiqh worship learning is more assist students in understanding the implementation of worship fiqh. Key words: aplication of simulation methode, Fiqh learning of MTs, teacher planning